Impact performance of hat-stiffened composite panels reinforced with I-beam - Uslu, Merve; Kaman, Mete Onur; Yanen, Cenk; Albayrak, Mustafa; Dag, Serkan; Erdem, Serkan; Turan, Kadir (Walter de Gruyter Gmbh, 2026)
In this study, hat-stiffened composite panels, which are widely employed in the aerospace industry, were fabricated using the vacuum infusion method. To enhance the strength of the hat-stringer composites, a composite I-beam was integrated into the panel, and its impact performance under low-velocity loading was investigated. It was determined that the incorporation of the I-beam into the hat-stiffened composite panels increased the maximum impact force by up to 2.5 times. For the numerical analyses, the LS-DYNA finite element software package was utilized, and the impact test results were examined in three dimensions based on the Hashin failure criterion. Geometric variations that occurred in the hat-stringer and I-beam during the manufacturing process were incorporated into the numerical model. The correlation between the experimental data and the modified numerical results is presented in detail.
Keywords: low velocity impact; Hashin criteria; stiffened panels; production effect on composite; strengthened composites